Field study of diffuse ceiling ventilation performance under high air change rate - Tougne, Gael; Hviid, Christian A. (CLIMA 2022 conference, 2022)
Diffuse ceiling ventilation utilizes the entire ceiling surface to distribute airflow to rooms. The air seeps via perforations, often present in acoustic ceilings, from the pressurized plenum to the occupied zone below. In the literature, this concept has proven superior in terms of draught, even for quite high airflow rates and sub-temperatures. However, documentation of practical installations followed by measurements campaigns and in-depth analyses of the concept, are rare. Consequently, we present a study to showcase the performance of the installation under rather extreme conditions: air change rate of 20 h-1 and supply temperature 3- 4°C below room temperature. The corresponding cooling was 56-74 W//m2. The investigated room was 165m² and 2.75m high. Numerous computers and TV screens caused significant heat loads, as well as the large windows on 3 facades of the room (West, North, East). The ventilation, equipped with a cooling coil, supplied 9200 m³/h to maintain the temperature in the room. The airspeeds and temperatures were measured at 7 different heights (from 0.1m to 2.4m) in 26 positions. The results showed an even distribution of the temperature in the room with measurements between 23 and 26˚C and an average temperature gradient of 0.33˚C/m (max 0.8˚C/m) while in the plenum the difference of temperature was 1.5˚C between the inlet and the opposite corner. The airspeeds were on average between 0.11 m/s and 0.17 m/s with the highest values at the ankle level. Half of the logged points had Draught Rate (DR) below 10% and all positions were below 20% except one. The airspeed exceeded 0.2m/s in less than 9% of the measurements. For comparison, we discuss the implications of using ceiling swirl diffusers or displacement ventilation in the same context.